Early stimulation as a neurological program in language skills and abilities in early childhood children in Ecuador - Zambrano Pintado, Ruth (2022)
Early stimulation are educational techniques, used in children in the infant stage (0-10 years) to correct cognitively, socially and emotionally; psychomotor disorders to stimulate compensatory capacities.The objective of the research is to demonstrate the importance of early stimulation as a response to the need to use educational activities that allow the child to counteract psychomotor skills and abilities and cognitive language, which contributes to a beneficial incorporation into society.The research paradigm is positivist with a quantitative approach, a non-experimental type with a documentary and empirical source. Considering the study space is field and longitudinal, and the level is explanatory.The population is made up of 200 children of initial education II from Ecuadorian Educational Units located in the canton of Ambato, Ecuador; in ages between three and five years.The measurement instruments used were the Ortiz Abbreviated Development Scale and the ELA-Albor Test.The results indicate that once the values of the instruments were used and analyzed in their phases I and II (pretest and posttest), in a period of time between each one of 6 months, improvements were observed in the participants in terms of development psychomotor and linguistic, showing that repetitions and reinforcements between the trident (children, educators and parents) are effective for the evolution of the minors evaluated. The conclusions indicate that an adequate use of early stimulation programs guarantees the strengthening of neurodevelopmental activities, which help the emotional stability of the child, to function socially.